Biologics for the treatment of moderate- to-severe ulcerative colitis in pediatric patients - Albenberg LG; Mamula P; Kelsen JR (Dove Medical Press, 2012)
Lindsey G Albenberg, Petar Mamula, Judith R KelsenDivision of Gastroenterology, Hepatology, and Nutrition, The Children's Hospital of Philadelphia, Philadelphia, PA, USAAbstract: Ulcerative colitis (UC) is a chronic, inflammatory disease of the large intestine. In pediatric patients, UC is associated with significant morbidity including persistent symptoms affecting quality of life, hospitalizations, and surgery, and therapeutic strategies are limited. The advent of biologics, specifically anti-tumor necrosis factor- α medications, has been very beneficial for pediatric patients suffering from UC. Since the introduction of these therapies, there has been improvement in the rates of both remission as well as colectomy-free survival. However, there has been concern regarding the adverse events associated with these medications including the risk of infection and malignancy. The efficacy and safety of infliximab, the most frequently used biologic medication in pediatric patients with UC, will be the focus of this review.Keywords: ulcerative colitis, biologics, anti-TNF-α, infliximab, adalimumab